Jihadist Threat to India: the Case for Islamic Reformation by an Indian Muslim - "Ahmad, Tufail" (JAipur, 2016)
ufail Ahmad is a journalist and commentator on jihadist movements of South Asia. As the support to ISIS is growing among Indian Muslims, his book comes as a basic text to understanding Islamic radicalisation. The book is a collection of Ahmad's research papers and newspaper columns. It offers a profound understanding of jihadist organisations based in Pakistan and how the Pakistani state's support to them undermines peace in Afghanistan and India. The reader comes to grasp that the Arab Spring failed because of the absence of an infrastructure of liberal ideas, which means that jihadist organisations like ISIS find a ready audience in countries from India to the Middle East thanks to the presence of an infrastructure of ideas supportive of everyday Islamism. While this book is relevant for military and intelligence analysts, Ahmad's columns posit the idea that Indian democracy has emerged as the best living space for Muslims.
Keywords: Islam